Impact of communication on first treatment decisions in people with relapsing-remitting multiple sclerosis. Issue 12 (December 2020) - Manzano, Ana; Eskytė, Ieva; Ford, Helen L.; Bekker, Hilary L.; Potrata, Barbara; Chataway, Jeremy; Schmierer, Klaus; Pepper, George; Meads, David; Webb, Edward JD; Pavitt, Sue H
Highlights: Multiple new treatments are available for relapsing remitting multiple sclerosis. Knowledge of disease, impact and prognosis is insufficient to make first choices. Doctors and patients use different filtering mechanisms in decisions. Clinical and psycho-social factors are important for patients in decisions. Patient decision aids should consider first and consecutive decisions. Abstract: Objective: Disease-Modifying Treatments (DMTs) have contributed to a new clinical landscape for people with relapsing-remitting multiple sclerosis (pwRRMS). A challenge for services is how to support DMT decisions with changing clinical evidence, and differing treatment goals. This article investigates how pwRRMS weigh up the pros and cons of DMTs by examining how communication at the point of diagnosis is related to DMT decisions. Methods: 30 semi-structured interviews with pwRRMS in England were conducted using a theoretical purposive sampling strategy and analysed using the thematic approach to answer: How does communication about RRMS during diagnosis influence decisions about when and which DMT to choose? Results: Three meta-themes were identified: a) communication context; b) delayed communication and hope for people with "non-active" RRMS at diagnosis; c) people with "active" RRMS at diagnosis: Conflated, generic, selective and simplified information Conclusion: At the time of diagnosis, patient–physician interactions are characterised by emotions and information complexity. Clinical, social and psychological DMT filtering mechanisms are activated during first decisions. Personalised evidence is needed to make informed decisions. Practice implications: Patient decision aids should consider first and consecutive decisions and should not encourage a false sense of large choices that could add to decision anxiety.